Absolute │A; δ │k and │A; γ; δ│k Summability for n-tupled Triangle Matrices - Sonker, Smita; Munjal, Alka; Mishra, Lakshmi Narayan (Journal of Nepal Mathematical Society, 2020)
In this study, new sequence spaces (Ak; δ) & (Ak; γ; δ) have been introduced to establish two theorems on minimal set of the sufficient conditions for a n-tupled triangle T to be a bounded operator on sequence spaces (Ank ; δ) & (Ank ; γ; δ): Generalized summability method │A; δ │k & │A; γ; δ│k have been applied for determining the sufficient conditions, where k ≥ 1; δ ≥ 0 and γ is real number. Further, a set of new and well-known applications has been deduced from the main result under suitable conditions, which shows the importance of the main result.